1995
DOI: 10.1046/j.1469-0705.1995.06050313.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart screening in low‐risk pregnancies

Abstract: The aim of this study was to assess whether a screening program for fetal cardiac malformations is justified in a low-risk population, and which factors influence its accuracy. The fetal heart was evaluated in 7024 pregnant women at 20-22 weeks, and evaluation was repeated at a more advanced gestational age in 9% of cases. Cardiological follow-up was continued postnatally until 2 years of age. The overall prevalence of cardiac anomaly was 0.93%. The incidences of major and minor defects were 0.44% and 0.48%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 0 publications
8
70
0
3
Order By: Relevance
“…CAT and PA-VSD represent two rare subgroups of conotruncal anomalies particularly difficult to differentiate in fetal life [3,15,16,17]. Our overall diagnostic accuracy was 81%, which is inside the range of 77-96% previously reported [1,2,3,4,18,19], although the GA at diagnosis was lower in our series.…”
Section: Discussionmentioning
confidence: 40%
“…CAT and PA-VSD represent two rare subgroups of conotruncal anomalies particularly difficult to differentiate in fetal life [3,15,16,17]. Our overall diagnostic accuracy was 81%, which is inside the range of 77-96% previously reported [1,2,3,4,18,19], although the GA at diagnosis was lower in our series.…”
Section: Discussionmentioning
confidence: 40%
“…Unfortunately, most population studies regarding the use of ultrasonography to detect congenital heart disease have reported low sensitivities for abnormalities of the great arteries [10,12,13,28,41,42,63,64]. Studies documenting higher detection rates emphasized routine visualization of the outflow tracts in addition to the usual four-chamber view [8,22,24,25,27,32,36,37,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal echocardiography in the second or (more recently) the first-trimester of pregnancy has been found to be a promising screening method for CHDs. Evaluation of the four-chamber view of the heart and the outflow tracts in the second-trimester of pregnancy yielded a sensitivity as high as 61% [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Combined examination of the four-chamber and outflow tract views of the heart in the second-trimester led to the identification of 61% of the fetuses with CHDs [5]. The detection rate was further increased to 81% when transvaginal ultrasound was used to predict fetal cardiac defects in a small series [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%